Increasing Farmer Groups Capacity in Cempaka District through the Utilization of Mobile-Based Knowledge Management and Strengthening Digital Literacy - Putra, Pacu; Oktadini, Nabila Rizky; Irmawati, Irmawati; Meiriza, Allsela; Sevtiyuni, Putri Eka (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Kelompok Tani (Poktan) Hidup Baru is located in Cempaka District, East Ogan Komering Ulu (OKU) Regency, 123 km away from Sriwijaya University. Poktan Hidup Baru was established in 2020 by farmers in Cempaka District and is led by Ali Fauzan. With 29 members, most of them are rice and fruit farmers. The limited technology and literacy of the farmers means that they are not able to innovate. Therefore, the main problem in the Community Partnership Empowerment Programme is the lack of digital literacy and agricultural knowledge management skills. Therefore, this PKM programme aims to introduce knowledge management and improve farmers' skills in using the internet and mobile-based agricultural applications. In addition, this PKM programme also aims to support the transformation of higher education through the production of scientific publications and audio-visual works.Service activities are carried out in five stages: first, preparation; second, production of materials; third, advice; fourth, support; and fifth, monitoring.  The team provides advice and training on the culture of knowledge sharing and the use of agricultural applications such as Plantix. This application can help solve agricultural problems in identifying pests and plant diseases, irrigation and marketing agricultural products. The positive response from the Hidup Baru farmer group indicates the need for similar training in the future to improve farmers' knowledge and skills.